2019
DOI: 10.1177/1548051819859289
|View full text |Cite
|
Sign up to set email alerts
|

Subtle and Overt Behaviors Toward Ethnic Minority Leaders and the Moderating Role of Competence

Abstract: This study extends research on stereotypes and leadership to consider the subtle and overt behavioral responses to leaders from multiple ethnic backgrounds. Specifically, the study focuses on overt and subtle discrimination toward African American, Asian American, Middle Eastern American, and White male leaders. Results from an experiment measuring authentic reactions to leaders reveal that Asian American leaders were treated more negatively in comparison to White and Middle Eastern American leaders. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Incorporating qualitative results, the importance of diversity in senior positions ( α = 0.92), was quantitatively examined using scales adapted from Anderson et al ’s (2019) importance of ethnical minority leader scale. The revised scales measured the importance of gender and race at the execute level.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating qualitative results, the importance of diversity in senior positions ( α = 0.92), was quantitatively examined using scales adapted from Anderson et al ’s (2019) importance of ethnical minority leader scale. The revised scales measured the importance of gender and race at the execute level.…”
Section: Resultsmentioning
confidence: 99%
“…The stereotypical leader prototype that discourages women from applying for and achieving management positions has a similar effect on minority workers. Organizational leaders are rated more highly by subordinates and superiors when they possess characteristics that align with the rater's beliefs about a prototypical leader (Eagly & Karau, 2002), and research has shown that the prototypical leader persona is based on a white male (Anderson et al, 2019;Kossek & Buzzanell, 2018;Mungaray & Curtin, 2021;Rhode, 2017;Rosette et al, 2008). Minority employees that do not have a selfperception that includes these qualities may face limited access to promotions and senior level leadership positions (Mungaray & Curtin, 2021).…”
Section: Barriers To Leadership For Minoritiesmentioning
confidence: 99%